Overexpression of microRNA OsmiR397 improves rice yield by increasing grain size and promoting panicle branching - Zhang, Yu-Chan; Yu, Yang; Wang, Cong-Ying; Li, Ze-Yuan; Liu, Qing; Xu, Jie; Liao, Jian-You; Wang, Xiao-Jing; Qu, Liang-Hu; Chen, Fan; Xin, Peiyong; Yan, Cunyu; et al. (Nature biotechnology, 2013)
Overexpression of a microRNA in rice increases yield, suggesting new routes to crop improvement. Increasing grain yields is a major focus of crop breeders around the world. Here we report that overexpression of the rice microRNA (miRNA) OsmiR397, which is naturally highly expressed in young panicles and grains, enlarges grain size and promotes panicle branching, leading to an increase in overall grain yield of up to 25% in a field trial. To our knowledge, no previous report has shown a positive regulatory role of miRNA in the control of plant seed size and grain yield. We determined that OsmiR397 increases grain yield by downregulating its target, OsLAC , whose product is a laccase-like protein that we found to be involved in the sensitivity of plants to brassinosteroids. As miR397 is highly conserved across different species, our results suggest that manipulating miR397 may be useful for increasing grain yield not only in rice but also in other cereal crops.